Blood transfusion therapy for β‐thalassemia major and hemoglobin E β‐thalassemia: Adequacy, trends, and determinants in Sri Lanka. Issue 5 (29th January 2019) - Mettananda, Sachith; Pathiraja, Hashan; Peiris, Ravindu; Wickramarathne, Nethmi; Bandara, Dayananda; de Silva, Udaya; Mettananda, Chamila; Premawardhena, Anuja
Abstract: Background: Regular blood transfusion therapy still remains the cornerstone in the management of β‐thalassemia. Although recommendations are clear for patients with β‐thalassemia major, uniform transfusion guidelines are lacking for patients with hemoglobin E β‐thalassemia. In this study, we aim to describe the adequacy, trends, and determinants of blood transfusion therapy in a large cohort of pediatric patients with β‐thalassemia major and hemoglobin E β‐thalassemia. Methods/procedure: This cross‐sectional study was performed among all regularly transfused patents with β‐thalassemia aged 2 to 18 years attending three large thalassemia centers in Sri Lanka. Data were collected using an interviewer‐administered questionnaire, perusal of clinical records, and physical examination of patients by trained doctors. Results: A total of 328 patients (male 47%) were recruited; 83% had β‐thalassemia major, whereas 16% had hemoglobin E β‐thalassemia. Sixty‐one percent of patients had low pretransfusion hemoglobin levels (< 9.0 g/dL) despite receiving high transfusion volumes (> 200 mL/kg/year) by a majority (56%). Median pretransfusion hemoglobin was significantly lower in patients with hemoglobin E β‐thalassemia compared with β‐thalassemia major ( P  < 0.001); however, there was no difference in requirement for high transfusion volumes over 200 mL/kg/year in both groups ( P  = 0.14). Hepatomegaly and splenomegaly were more common in hemoglobin E β‐thalassemia and were associated with lower pretransfusion hemoglobin. Transfusion requirements were higher among patients with hepatitis C and in those who are underweight. Conclusions: Over 60% of regularly transfused patients with β‐thalassemia have low pretransfusion hemoglobin levels despite receiving large transfusion volumes. Patients with hemoglobin E β‐thalassemia are undertransfused and specific recommendations should be developed to guide transfusions in these patients.